An Ionic Liquid Ablation Agent for Local Ablation and Immune Activation in Pancreatic Cancer. Issue 10 (25th January 2023) - Huang, Junming; Wang, Meng; Zhang, Fu; Shao, Shiyi; Yao, Zhuo; Zhao, Xinyu; Hu, Qida; Liang, Tingbo
Abstract: Pancreatic ductal adenocarcinoma rapidly acquires resistance to chemotherapy, remaining a fatal disease. Immunotherapy is one of the breakthroughs in cancer treatment, which includes immune checkpoint inhibitors, chimeric antigen receptor T‐cell immunotherapy, and neoantigen vaccines. However, immunotherapy has not achieved satisfactory results in the treatment of pancreatic cancer. Immunogenic death comprises proinflammatory cell death, which provides a way to enhance tumor immunogenicity and promote an immune response in solid tumors. Herein, an ionic liquid ablation agent (LAA), synthesized from choline and geranic acid, which triggers necrosis‐induced immunotherapy by remodeling an immunosuppressive "cold" tumor to an immune activated "hot" tumor is described. The results indicate that LAA‐treated tumor cells can enhance immunogenicity, inducing dendritic cell maturation, macrophage M1 polarization, and cytotoxic T lymphocyte infiltration. The results of the present study provide a novel strategy for solid tumor immunotherapy. Abstract : An ionic liquid (IL) agent comprising bicarbonate and geranic acid is engineered for ablation treatment of pancreatic cancer, providing a new method, IL ablation, to initiate and amplify the immune response against immune‐suppressive solid tumors, providing a potential solution to immunotherapy inefficiency.